Kayla a cry in the wilderness - Fennell, Tod.; Henderson, Meredith; Booth, Bronwen; Dooley, Brian; Merotte, Carl, 1959-; Czerny, Henry; Kendall, Nicholas; Van Steenwyk, Elizabeth (Chicago, Ill. : Questar, 2000)
Sam can't accept the trauma of what happened eight years ago: the disappearance and apparent death of his dad in the Arctic wilderness. Devoted to his father's memory, he despises his well-meaning, if awkward, stepdad and resents his mother for marrying this intruder. Sam's heart cry for companionship and understanding is finally answered by the appearance of a beautiful wild dog he names Kayla, after his dad's sled dog. Sam bonds with Kayla, whose actions teach the boy about love, loyalty, and self-sacrifice.
Based on a novel by Elizabeth Van Steenwyk.
Produced in association with WIC Entertainment by Cine- Action.
Special features include a biography of the author, historical background, thoughts to be shared, previews of additional films, scene index.
Director of photography, John Berrie ; editor, Jean-Marie Drot ; composer, Milan Kymlicka.
Tod Fennell, Meredith Henderson, Bronwen Booth, Brian Dooley, Carl Merotte, Henry Czerny.
DVD.
Keywords: DVD-Video discs; DVDs; Sled dog racing -- Drama; Remarriage -- Drama; Death -- Drama; Action and adventure films; Feature films; Montana -- Drama